Penerapan Terapi Genggam Jari dan Nafas dalam terhadap Tekanan Darah pada Penderita Hipertensi di Kecamatan Mojosongo Kota Surakarta - Sofyan Mahendra Firdaus; Eska Dwi Prajayanti (STIKes Ibnu Sina Ajibarang, 2024)
Background: The prevalence in the world according to WHO data (2020) is approximately 972 million people or 26.4% of the population with hypertension. The prevalence rate in Surakarta City, Jebres sub-district is 92,614 people, Mojosongo village is the first with a prevalence of hypertension incidence of 12,447 patients. The development of complementary medicine has a very rapid percentage increase. Globally, complementary therapy to reduce blood pressure has been widely practiced, for example, such as finger clasp therapy and deep breathing. Objective: Knowing the difference in blood pressure before and after the application of finger grip relaxation and deep breathing to lower blood pressure. Methods: Handling hypertension with finger grasping therapy is carried out on hypertensive patients with a research method carried out by means of before being given treatment / treatment, the variables are observed first (pretest) after which measurements are taken again after being given treatment (post test). Results: Handling hypertension with finger clasp therapy and deep breathing which is given once a day. This therapy is given for 1 day, the therapy is carried out for 30 minutes in one meeting. This therapy can reduce the patient's blood pressure. Conclusion: Finger grasping therapy and deep breathing can reduce high blood pressure in patients with hypertension.